The Influence of Group Investigation Learning Model Assisted by Three-Dimensional Media on Mathematics Learning Outcomes - Sabili, Ahmad Enggal; Herpratiwi, Herpratiwi; Mashari, Ali (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The aim of this study was to determine the effect of cooperative learning model type group investigation assisted by three-dimensional media on the learning outcomes of fifth grade students of SDN 1 Jati Indah South Lampung. This type of research is a qualitative type of pre-experimental design in the form of one group pretest posttest. The population in this study were fifth grade students of SDN 1 Jati Indah South Lampung. The probability sampling technique of simple random sampling type was used as a sampling technique. Tests and documentation were used in data collection methods and equipment. T-test (paired sample t-test) is the method to analyze the data. The results showed the t-count of 10.778 with the level of Sig. (2-tailed) 0.000 < 0.05. Also reinforced by the average results of pretest 63.3 and posttest 73.5. Based on this, that there is an effect of cooperative learning model type group investigation assisted by three-dimensional media on mathematics learning outcomes.